Enhancing Knowledge Management In The Era Of Industry 4.0 For Project Success - Chong, Man Foong (2021)
Knowledge management is crucial when it comes to project success. In recent years, the importance of knowledge management in project management has become one of the important factors for project managers to achieve project success. In the era of digitalization, the introduction of the smartphone, artificial intelligence, and digital product is continuously changing our daily habits. The purpose of this dissertation is to gain an understanding of the methods that can be used to enhance knowledge management in the era of industry 4.0 for project managers to achieve better project success. For the study, a quantitative technique is utilised to assess the impacts of one set of variables on another set of variables identified. This aided in the collection of data from the intended population under study and the generalization of results based on numeric quantification. The findings suggested that new technologies in Industry 4.0 era make it easier to collect massive volumes of data, which may then be utilized to improve operational operations in terms of efficiency, productivity, and flexibility for project success. Total 330 respondents will be selected for the survey in this study. The sampling frame of this study will be the companies representatives who participating in project management and knowledge management systems in relation to Industry 4.0 practices. The study has the practical implications that it highlights the need to pay adequate attention to specific concepts/technologies introduced by Industry 4.0 for better project management. The study contributes through the findings that information in the Industry 4.0 environment originates mostly from knowledge sources, as a result, KM4.0 and project success are linked.